Dampak Usaha Bengkel Las Terhadap Pendapatan Pekerja Di Kecamatan Cakranegara Kota Mataram - Mimi Cahayani (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
Economic development can be carried out if the community plays an active role in making an effort to create income in the community.One form of business that can be done is a welding shop business. In this study conducted in the District cakranegara which has absorbed labor.So it is necessary to know whether the welding shop business has an impact on the income of workers. To find out, a case study research method is used with a qualitative approach.Data validation to check the validity of the data using source triangulation techniques.The results of the study showed that welding workshops in the sub-district of cakranegara had a positive impact on the income of workers where workers who were more senior and more skilled would have more income so that every worker would not hesitate to continue to develop a career here. Income per day from coolies will vary in each workshop and ranges between Rp. 25,000 thousand to Rp. 40,000 thousand. The monthly income of coolies calculated by the number of working days, from Monday to Saturday, ranges from Rp. 650,000 up to Rp.1,080,000.As for the handyman ranging from Rp. 1,040,000 up to Rp. 1,620,000. The average income earned is Rp. 1,500,000.00 up to Rp. 1,600,000.